Penerapan Teknik Nesting Pada Asuhan Keperawatan Bayi Bblr Di Ruang Bayi Rsud DR. H. Moch Ansari Saleh Banjarmasin - Baidah; M.Husni; Laili Muthia Ghina (CV. ITTC INDONESIA, 2024)
LBW births lead to a variety of serious health problems. The application of nesting techniques can help babies show a good general condition. The purpose of the study was to apply the nesting technique to the nursing care of LBW babies. This study used a case study design with a nursing care approach that focuses on the application of nesting techniques in LBW babies. The results of the study for 20 days showed that the patient's oxygen saturation was between 95-100%, without the use of oxygen aids. The use of nesting contributes to increasing body weight and maintaining the stability of pulse frequency, body temperature and respiration. In conclusion, nesting in LBW infants has an influence on body temperature, oxygen saturation, body weight and pulse frequency. It is suggested that nurses apply nesting on an ongoing basis to ensure proper and rapid recovery and stabilization of vital signs of LBW infants.